Moisture, ash and fat composition of Pangasianodon Hypophthalmus (Sauvage, 1878) and Pangasius Nasutus (Bleeker, 1863) - Zulkiflee, Siti Zulaikha; Yusof, Muhammad Fitri; A. Rahman, Nor Azlina; Rostam, Muhamad Ashraf (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia., 2020)
Introduction: The purpose of the study is to analyse the moisture, ash and fat composition of Pangasianodon hypophthalmus (Sauvage, 1878) and Pangasius nasutus (Bleeker, 1863) by using proximate analysis. Methods: The specimens for P.hypophthalmus were collected from Institute of Oceanography and Maritime Studies (INOCEM) Hatchery, Kuantan, Pahang. A total of four fishes were taken with an average weight of 0.6kg and length of 38 cm. Specimens of P.nasutus which are wild fish were caught from Pahang river at Pekan, Pahang. A total of two fishes were caught with the total average weight of 1.1kg and length of 45cm. The independent-samples t-test and one-way ANOVA by SPSS version 12.0 software were used to analyze the results for objective one and two respectively. Each analysis was repeated three times. Results: There is no significant difference for moisture content between both species, however, there is a significant different in ash and fat content between P.hypophthalmus and P.nasutus. Conclusions: This study indicates that species P.hypopthalmus and P.nasutus shares similar nutrient composition.